Mi vida en un baile de joropo (2022)
This degree work aims to make visible in a descriptive way, the artistic life from the beginning, teaching processes, participation in festivals and dance meetings of Master Jerci Tumay Tabaco, being the joropo dance the door for the construction of his life project. , with a qualitative approach, using the interview as a tool for collecting information from the artistic work developed by the teacher inside and outside the Llanero territory. This material becomes a reference document since it narrates part of an identity, the richness and cultural diversity that is alive in the Colombian plains and leaves as a vestige the characteristic features, in practice, promotion and conservation of a cultural manifestation experienced by a cultivator and teacher of the llanera dance. To carry out this degree work, interviews were carried out with their high school teachers, other participants in llaneros festivals and dance meetings, dance teachers, as well as students from the llanera region and students from other regions of Colombia. This autobiographical account allows us to remember everything lived, experienced and worked to achieve the goals and purposes in the different stages of Jerci Tumay's life. To remember is to relive and write down all these experiences, somehow, it becomes something very significant for the master Jerci, because it is to reveal his steps, his processes and creative, competitive spaces and all the experiences that led him to build his route as a joropo trainer, as a dancer and contestant and the way in which he adapted to different contexts inside and outside the llanera region